2013
DOI: 10.12795/pixelbit.2013.i43.10
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de twitter en la comunicación y promoción institucional de las universidades Impact of twitter on communication and institutional promotion of universities

Abstract: La presente investigación estudia la presencia y actividad de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
3
0
2
Order By: Relevance
“…Regarding the use of hashtags, the results are in line with those of Guzmán Duque et al [58] in their study on the impact of the use of Twitter in the organizational field. In this work, the authors highlighted the potential of these markers in facilitating the promotion and projection of the organization to the audience.…”
Section: Volumes Components and Publication Moments That Increase Content Recognition (Rqi)supporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the use of hashtags, the results are in line with those of Guzmán Duque et al [58] in their study on the impact of the use of Twitter in the organizational field. In this work, the authors highlighted the potential of these markers in facilitating the promotion and projection of the organization to the audience.…”
Section: Volumes Components and Publication Moments That Increase Content Recognition (Rqi)supporting
confidence: 89%
“…Along the same lines, there are studies that indicate that organizations should not settle for using their accounts to build their institutional image but rather must also protect the reputation of the organization [57]. Some authors claim that properly managed, social network services can even serve as a customer acquisition tool [58].…”
Section: Discussionmentioning
confidence: 99%
“…These platforms were not only used for educational purposes but also to promote their institutions aiming at recruiting potential students. This idea was corroborated by the study conducted by Guzmán Duque et al (2013), which examined the hashtag contents of Twitter accounts belonging to the top 200 universities in Shanghai Ranking. This study identified two predominant trends: stimulating communication and interaction within the university community and disseminating corporate information.…”
Section: Marketing In Spanish Universities: An In-depth Look At Its E...mentioning
confidence: 84%
“…Subsequently, nine more universities joined in the same year, reaching an 86.9% adoption rate by July 2012 (Paniagua Rojano et al , 2012). Although Twitter was soon regarded as a powerful catalyst for communication and educational interaction within the university community (Guzmán Duque et al , 2013), research conducted on the contents and activity volume of Spanish universities on Twitter during these early years revealed a notable deficiency in terms of communication effectiveness and impact. Rodríguez Ruibal and Cristino (2012) conducted a quantitative analysis on the Twitter engagement of all the Spanish universities in 2012.…”
Section: Marketing In Spanish Universities: An In-depth Look At Its E...mentioning
confidence: 99%
“…RACIAS al desarrollo de Internet y al interés de la población por incrementar su participación en los procesos de toma de decisión de las instituciones, han aparecido diferentes herramientas que, aprovechando las particularidades del entorno digital, han Navarida, 2012; Guzmán et al, 2013).…”
Section: Introductionunclassified